Path Constitution Analysis: A Methodology for Understanding Path Dependence and Path Creation - Jörg Sydow; Arnold Windeler; Gordon Müller-Seitz; Knut Lange (BuR - Business Research, 2012)
Although an increasing number of studies of technological, institutional and organizational change refer to the concepts of path dependence and path creation, few attempts have been made to consider these concepts explicitly in their methodological accounts. This paper addresses this gap and contributes to the literature by developing a comprehensive methodology that originates from the concepts of path dependence and path creation path constitution analysis (PCA) and allows for the integration of multi-actor constellations on multiple levels of analysis within a process perspective. Based upon a longitudinal case study in the field of semiconductors, we illustrate PCA in action as a template for other researchers and critically examine its adequacy. We conclude with implications for further path-oriented inquiries.
urn:nbn:de:0009-20-35046
Keywords: 650; multilevel approach; path constitution analysis; path creation; path dependence; process data; qualitative methodology; Pfadabhängigkeit; Qualitatives Verfahren; Wissenschaftliche Methode; Operations Research